1992
DOI: 10.1111/j.1471-0528.1992.tb14462.x
|View full text |Cite
|
Sign up to set email alerts
|

Breech delivery and epidural analgesia

Abstract: Objective To examine the effect of epidural analgesia on the progress and outcome of spontaneous labour in women with a singleton breech presentation at term (3=37 weeks). Design A retrospective study. Setting Data Bank, Aberdeen Maternity Hospital. Subjects 643 women (273 primiparae and 370 multiparae) with a singleton breech presentation and spontaneous onset of labour at term. Outcome measures Duration of labour; augmentation of labour with oxytocin infusion; caesarean section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 22 publications
0
16
2
Order By: Relevance
“…Earlier studies have shown that epidural anesthesia in connection with breech delivery is associated with a longer duration of labor and an increased need for augmentation of labor with oxytocin infusion [28]. It is not possible to tell whether the association between epidural anesthesia and adverse outcome is due to the epidural prolonging labor and delaying expulsion of the fetus or whether epidural anesthesia is simply used more in prolonged labors that inherently have a higher risk of expulsive delay and adverse outcome [11].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that epidural anesthesia in connection with breech delivery is associated with a longer duration of labor and an increased need for augmentation of labor with oxytocin infusion [28]. It is not possible to tell whether the association between epidural anesthesia and adverse outcome is due to the epidural prolonging labor and delaying expulsion of the fetus or whether epidural anesthesia is simply used more in prolonged labors that inherently have a higher risk of expulsive delay and adverse outcome [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Chadha et al (1992) have shown that women admitted in labour with breech presentation at a low cervical dilatation (less than 3 cm) are more likely to be delivered by caesarean section. This is in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%
“…77 They observed that epidural was associated with over a fivefold increase in caesarean section in the second stage of labour (odds ratio 5.4, 95% CI 2.5 -12.0). In a very large retrospective study from the United Kingdom, Chadha et al concluded that epidural analgesia was associated' with longer labours, increased requirement for augmentation, and increased caesarean section.…”
Section: Use Of Epidural Analgesia With Vaginal Birth After Caesareanmentioning
confidence: 98%